Biblical Critical Literacy for High School Students: Exploring the Character of King David - Simanjuntak, Marudut Bernadtua; Sutrisno, Sutrisno; Hutabarat, Christiani (MAHABBAH: Journal of Religion and Education, 2025)
This research investigates the transformative role of biblical, theological, Christian religion, and teenage education, focusing on high school students' engagement with the character of King David. Through qualitative descriptive methods, insights were gathered from participants in Christian schools and youth groups, highlighting the impact of biblical literacy on adolescents' spiritual development and moral reasoning. Findings underscored the significance of integrating biblical narratives and theological teachings in educational frameworks to cultivate a deep understanding of Christian values and virtues. The study advocates for holistic approaches that foster ethical leadership and personal growth among teenagers, emphasising the role of parental involvement and community support in nurturing adolescents' faith journeys.